(untitled) (Research, Society and Development, 2021)
Fungi are source of polysaccharides that can show biological activity. The objective of this research was obtained polysaccharides from Periconia byssoides and evaluate antibacterial and hypoglycemic activity in vitro. The number-average molecular weight and degree of polymerization were determined. The results show that the polysaccharide of P. byssoides has potential as hypoglycemic. Therefore, it would be interesting to conduct in vivo research with this polysaccharide, to know about its hypoglycemic activity.